Fabric phase sorptive extraction for the determination of 17 multiclass fungicides in environmental water by gas chromatography‐tandem mass spectrometry. Issue 9 (5th February 2020) - Celeiro, Maria; Vazquez, Lua; Nurerk, Piyaluk; Kabir, Abuzar; Furton, Kenneth G.; Dagnac, Thierry; Llompart, Maria
Abstract: A rapid environmental pollution screening and monitoring workflow based on fabric phase sorptive extraction‐gas chromatography‐tandem mass spectrometry (FPSE‐GC‐MS/MS) is proposed for the first time for the analysis of 17 widespread used fungicides (metalaxyl, cyprodinil, tolylfluanid, procymidone, folpet, fludioxonil, myclobutanil, kresoxim methyl, iprovalicarb, benalaxyl, trifloxystrobin, fenhexamid, tebuconazole, iprodione, pyraclostrobin, azoxystrobin and dimethomorph) in environmental waters. The most critical parameters affecting FPSE, such as sample volume, matrix pH, desorption solvent and time, and ionic strength were optimized by statistical design of experiment to obtain the highest extraction efficiency. Under the optimized conditions, the proposed FPSE‐GC‐MS/MS method was validated in terms of linearity, repeatability, reproducibility, accuracy and precision. To assess matrix effects, recovery studies were performed employing different water matrices including ultrapure, fountain, river, spring, and tap water at 4 different concentration levels (0.1, 0.5, 1 and 5 µg/L). Recoveries were quantitative with values ranging between 70–115%, and relative standard deviation values lower than 14%. Limits of quantification were at the low ng/L for all the target fungicides. Finally, the validated FPSE‐GC‐MS/MS method was applied to real water samples, revealing the presence of 11 out of the 17 target fungicides.